Association Between Irregular Eating Behavior, High Fat Intake, and Dyspepsia Syndrome of Male Adolescents at Selected Senior High School in Yogyakarta - Nugraha, Adityansyah Irendra; Maduseno, Sutanto; Ratnasari, Neneng (Faculty of Medicine Universitas Gadjah Mada, 2021)
Background. Dyspepsia syndrome is a group of symptoms consisting of epigastric discomfort, nausea, vomiting, bloating, early satiety, abdominal fullness, and belching. Dyspepsia syndrome is common in male adolescents. The causes of dyspepsia are multifactorial, one of the most common is diet and lifestyle changes. Objective. The aim of this study is to determine the association between irregular eating behavior, high fat intake, and dyspepsia syndrome of male adolescents in Yogyakarta senior high school.Methods. A cross-sectional study was performed among 255 male adolescents aged 15-19 years in Yogyakarta senior high school. The data were obtained using Gastrointestinal Symptoms (GIS) questionnaire, irregular eating behavior questionnaire, and Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Nominal variables were analyzed statistically by chi-square test and logistic regression test, numerical variables were analyzed by Mann-Whitney test and linear regression test. Result. Dyspepsia syndrome is positive in 54.9% of the subject. Seventy-four percent of subjects with irregular eating behavior had dyspepsia, p<0.001, OR 3.58 (CI 95%, 2.05-6.26). Seventy-five percent of subjects with high fat intake had dyspepsia, p= 0.005, OR 2.86 (CI 95%, 1.33-6.15). The median GIS score of the high fat and normal fat intake group are two to one (p=0.005). Median GIS scores of irregular and regular eating behavior groups are two to zero (p<0.001). The coefficient of determination (R2) from multivariate analysis is 0.065.Conclusion. There is a significant association between eating irregularities and high fat consumption patterns with the incidence of dyspepsia syndrome in male adolescents in Yogyakarta high school.